Rehabilitation with intensive attention training early after acquired brain injury promotes better long-term status on health-related quality of life, daily activities, work ability and return to work - Gabriela Markovic; Aniko Bartfai; Marie-Louise Schult; Jan Ekholm (Journal of Rehabilitation Medicine, 2024)
Objective: To describe long-term effects on activity, participation, and quality of life (i) at different post-injury starting time points of attention training and (ii) of two different types of rehabilitation with attention training in patients after stroke or traumatic brain injury; and to describe their functioning level.